A concise approach to the tricyclic framework of longipinane- and ent-longipinane-type sesquiterpenoids. Issue 3 (3rd January 2019) - He, Min; Yi, Jiuzhou; Zhao, Gaoyuan; Chen, Peiqi; Long, Dan; Hu, Xiaojun; Li, Huilin; Xie, Xingang; Wang, Xiaolei; She, Xuegong
Abstract : A general strategy for the synthesis of the common 6, 6-dimethyltricyclic[5.4.0.0 2, 8 ]undecane framework of longipinane- and ent -longipinane-type sesquiterpenoids has been successfully developed. Abstract : A concise and efficient strategy for the synthesis of the common 6, 6-dimethyltricyclic[5.4.0.0 2, 8 ]undecane framework of longipinane- and ent -longipinane-type sesquiterpenoids has been developed. This approach features an intramolecular Diels–Alder reaction to construct the 6/7 cis -fused ring system and a Ti(iii )-mediated reductive radical cyclization reaction to access the highly strained bridged cyclobutane moiety.